Testing the Concept of Mitigating Urban Flooding with Permeable Road: Case Study of Tong Wei Tah Street, Kuching City, Sarawak, Malaysia - Darrien Yau Seng, Mah; Johnny Ong King, Ngu; Siti Noor Linda, Taib; Soh Fong, Lim; F.J., Putuhena (Walailak University, 2022)
This paper describes the investigation of permeable road as a mitigation measure for urban flooding. The study involves the reconstruction of a historical case of inundation, namely the 11 December 2019 flood event along the Tong Wei Tah Street in Greater Kuching City, Sarawak, Malaysia. The Storm Water Management Model version 5.0 was used as the platform to describe the flooding at the selected site and the functionality of permeable road to alleviate flooding. A permeable road with a dimension of 200 m long, 6 m wide and 1 m deep was used to simulate runoff after a structure was installed along the whole stretch of Tong Wei Tah Street. The model results show that flooding was caused by a backwater effect in the drainage system. Models predicted 0.1 to 0.5 m flood depths which matched the observed 0.3 m flood depth account of a local resident. The permeable road exhibited capability to absorb all the out-of-drain floodwaters, leaving no water due to the 11 December 2019 flood on the street. Modelling efforts demonstrated that the floodwater hydrographs in the drain rose and fell within 7 hours, while the underground storage, filled and drained within 13 hours. Moreover, the storage of permeable road was found to fill up to 75%, reserving the unfilled 25% for adverse weathers.